Strategi Coping Seseorang yang Mengalami Perceraian - Andria Pragholapati (NHM PRESS, 2022)
This study aims to examine the relationship of mental health problems with coping strategies of someone who is experiencing divorce in Bandung. Method: This research uses descriptive quantitative research design. The sample in this study amounted to 52 respondents selected as respondents using non-probability sampling with consecutive sampling. The questionnaire used was Ways of Coping. Data were analyzed quantitatively. Results: The results showed more than half of respondents (63.5%) used coping strategies focused on problems. Conclusions: Suggestions for psychiatrists is to improve coping strategies that focus on the problem of someone who is experiencing divorce.